FACTORS THAT AFFECT MOTOR VEHICLE TAXPAYER COMPLIANCE - Iqbal Rafikhul Fauzan; Vinny Stephanie Hidayat (COMPETITIVE, 2025)
The purpose of this study is to investigate how E-SAMSAT and tax penalties affect motor vehicle taxpayer compliance. All enrolled students in the Accounting Study Program at Maranatha Christian University make up the study's population.  Thirty-one responders were found based on the questionnaire distribution findings.  Explanatory research is the methodology employed.  Researchers utilize a sample technique called purposeful sampling.  SPSS 25 was used to test the data.  T-tests, f-tests, validity testing, reliability tests, and traditional (classical) assumption tests are among the data analysis techniques used.   The results of the study showed that E-SAMSAT had an effect on motor vehicle taxpayer compliance, while tax penalties had no effect.